Development communication research in the '90s - Gomez, Ely D. (1993)
The 2019 studies conducted in the Institute of Development Communication, UPLB from 1985 to 1990 included 149 undergraduate, 62 graduate and 8 staff research. A view of this research output revealed that majority (57.7%) of the studies may be labelled people-type research. This is followed by research on devcom processes and effects (21%) research on devcom institutions and structures (18.7%) and research on devcom planning and policies (2.8%).

The research methods used were : suvey (43%), multiple methods (19.6%), and quasi experiments (16.9%). The review indicated that research conducted during the period covered dealt mainly with farm families, extension workers, researchers, policy-makers and other members of the agricultural and rural system. The review showed that there was overdependence on the survey method.